ANALISA PENGARUH BEBAN KERJA, KOMUNIKASI DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA PEGAWAI BAGIAN UMUM BADAN PENYULUHAN DAN PENGEMBANGAN SDM KEMENTERIAN PERTANIAN - TIARA PRATIWI (2022)
This study aims to analyze the effect of workload, communication, and physical work environment on the performance of employees of the general section of Badan Penyuluhan dan Pengembangan SDM Kementerian Pertanian. The selected population is general section personnel badan penyuluhan dan pengembangan sdm kementerian pertanian using a saturated sample of 50 employees. The use of analytical tools in this study is Partial Least Square (PLS). The results obtained in this study are (1) Workload has a positive and significant effect on employee performance. (2) Communication has a positive and significant effect on employee performance. (3) Physical Work Environment has a positive and significant effect on employee performance. (4) there is a simultaneous influence on the performance of the Bagian Umum Badan Penyuluhan dan Pengembangan SDM Kementerian Pertanian.